eDNA-Based aquatic biodiversity monitoring in East and Southeast Asia: Current practices and priorities - Osathanunkul, Maslin; Minamoto, Toshifumi (Agriculture and Natural Resources, 2026)
Environmental DNA (eDNA) has revolutionized aquatic biodiversity monitoring by enabling sensitive, non-invasive detection of species from environmental samples. This review completed a comprehensive synthesis of eDNA research across East and Southeast Asia—a region with exceptional biodiversity and environmental challenges. Based on the evaluation of 890 peer-reviewed publications from 2008 to 2024, there have been rapid growth and methodological evolution in the field, dominated by research from China and Japan, with emerging contributions from Thailand and other Southeast Asian countries. The review highlights key advancements in eDNA methodologies, including species-specific assays, metabarcoding and the increasing adoption of digital polymerase chain reaction (dPCR). The performance of different sampling, preservation and detection strategies was discussed, along with the comparative advantages of eDNA over traditional monitoring approaches in terms of sensitivity, cost-effectiveness and reduced ecological disturbance. Critical challenges remain, including incomplete reference databases, quantification uncertainties and bioinformatic standardization. Future research priorities should enhance eDNA applications in tropical ecosystems, improve detection accuracy and promote integration into conservation policy and biodiversity management. This review has established a regional framework for advancing eDNA research and supporting sustainable aquatic biodiversity conservation in Asia.